2017
DOI: 10.1186/s40463-017-0185-3
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics of oropharyngeal squamous cell carcinoma: Opportunities for novel chemotherapeutic targets

Abstract: Epigenetic modifications are heritable changes in gene expression that do not directly alter DNA sequence. These modifications include DNA methylation, histone post-translational modifications, small and non-coding RNAs. Alterations in epigenetic profiles cause deregulation of fundamental gene expression pathways associated with carcinogenesis. The role of epigenetics in oropharyngeal squamous cell carcinoma (OPSCC) has recently been recognized, with implications for novel biomarkers, molecular diagnostics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 146 publications
(130 reference statements)
0
30
0
1
Order By: Relevance
“…EGFR expression was decreased in all cell lines upon treatment with curcumin, remaining consistent with current literature, as was EZH2. Given EZH2 overexpression to be associated with overall tumor aggressiveness in both HPV+ and HPV− cancers curcumin may provide an alternate means to repressing EZH2 expression over current modalities being tested …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EGFR expression was decreased in all cell lines upon treatment with curcumin, remaining consistent with current literature, as was EZH2. Given EZH2 overexpression to be associated with overall tumor aggressiveness in both HPV+ and HPV− cancers curcumin may provide an alternate means to repressing EZH2 expression over current modalities being tested …”
Section: Discussionmentioning
confidence: 99%
“…EGFR expression was decreased in all cell lines upon treatment with curcumin, remaining consistent with current literature, 23 as was EZH2. Given EZH2 overexpression to be associated with overall tumor aggressiveness in both HPV+ and HPV− cancers 38,39 curcumin may provide an alternate means to repressing EZH2 expression over current modalities being tested. [40][41][42] Tumor-suppressor protein p53 may be the only caveat to the claim of an apparent lack of HPV discrimination in drug agents, The gene expression results of the control treatments appear to be quite variable in comparison to one another.…”
Section: Immunofluorescencementioning
confidence: 99%
“…Compared to other head and neck neoplasms, oral squamous cell carcinoma (OSCC) compromise about 90% of the subtypes within this spectrum with~40%-50% mortality [1,2]. Research advances in the study of OSCC complexity have revealed that the induction and development of OSCC are due to a sum of genetic changes, epigenetic alterations, and environmental risk factors, especially tobacco, alcohol consumption, and viral infections [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, epigenetics play an important role in causing oral squamous cell carcinoma (OSCC). Epigenetics can be defined as the study of all heritable changes in gene phenotype and expression which are not coded in the DNA sequence [2,5,6]. Epigenetic alterations can cause major changes in the tumor progression, metastasis and response to chemo-radiotherapy [6].…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetics can be defined as the study of all heritable changes in gene phenotype and expression which are not coded in the DNA sequence [2,5,6]. Epigenetic alterations can cause major changes in the tumor progression, metastasis and response to chemo-radiotherapy [6]. The previously mentioned predisposing factors might act synergistically to a wide range of genetic and epigenetic events leading to suppression of tumor suppressor genes by promoting hyper-methylation and activation of OSCC oncogenesis [4].…”
Section: Introductionmentioning
confidence: 99%